Corporate lobbying: A review of the recent literature - Martin Gregor (Charles University in Prague, Institute of Economic Studies (IES), 2011)
This survey covers recent literature on lobbying, with particular focus on corporate lobbying. Three main research traditions – contests for policy rent, persuasion games, and multiple means models - are analyzed in detail. Various strategic aspects of lobbying are presented in the context of a single unified model that encompasses both strategic communication and monetary contributions. Next, the review investigates into three particular issues in the lobbying literature: (i) Incentive to lobby and the equilibrium amount of lobbying, both in the presence and absence of competitors, (ii) strategic substitution and complementarity of lobbying and contributions, and (iii) the role of intermediation in lobbying. Recent evidence from corporate lobbying is presented.
Keywords: D72; D82; D83; 330; lobbying; political contributions; menu auction; contest; persuasion